2007
DOI: 10.1134/s1068162007020021
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic fragments of the NS1 protein of the tick-borne encephalitis virus exhibiting a protective effect

Abstract: Potentially immunoactive regions of the NS1 nonstructural protein of the tick-borne encephalitis virus that can stimulate the antibody formation in vivo and protect animals from this disease were chosen on the basis of theoretical calculations. Eleven 16- to 27-aa peptides containing the chosen regions were synthesized. The ability of the free peptides (without any high-molecular-mass carrier) to stimulate the production of antipeptide antibodies in mice of three lines and ensure the formation of protective im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Several studies showed that NS1 immunization or passive transfer of anti-NS1 antibodies afforded protection against infections with flaviviruses, such as DENV, YFV and WNV in animal models [ 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. These findings have been confirmed for the TBEV NS1 protein [ 97 , 101 , 105 , 106 , 107 , 108 , 124 ]. Mouse studies showed that immunization with a synthetic peptide corresponding to the structurally conserved α-helix (aa37–55) of NS1 [ 108 ] or with various synthetic fragments of NS1 [ 101 ] induced partly protective immunity against lethal challenge infection with TBEV.…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 62%
See 4 more Smart Citations
“…Several studies showed that NS1 immunization or passive transfer of anti-NS1 antibodies afforded protection against infections with flaviviruses, such as DENV, YFV and WNV in animal models [ 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. These findings have been confirmed for the TBEV NS1 protein [ 97 , 101 , 105 , 106 , 107 , 108 , 124 ]. Mouse studies showed that immunization with a synthetic peptide corresponding to the structurally conserved α-helix (aa37–55) of NS1 [ 108 ] or with various synthetic fragments of NS1 [ 101 ] induced partly protective immunity against lethal challenge infection with TBEV.…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 62%
“…These findings have been confirmed for the TBEV NS1 protein [ 97 , 101 , 105 , 106 , 107 , 108 , 124 ]. Mouse studies showed that immunization with a synthetic peptide corresponding to the structurally conserved α-helix (aa37–55) of NS1 [ 108 ] or with various synthetic fragments of NS1 [ 101 ] induced partly protective immunity against lethal challenge infection with TBEV. In addition, significantly prolonged survival of TBEV-infected mice was observed after hyperimmunization with a whole recombinant TBEV NS1 protein, although all mice succumbed to infection [ 97 ].…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 62%
See 3 more Smart Citations